g-C3N4/Sn3O4 photoanode for H2 production: A promising photoelectrocatalyst for renewable energy generation - Romeiro, Fernanda da Costa [UNESP]; Perini, João Angelo Lima [UNESP]; Zanoni, Maria Valnice Boldrin [UNESP]; Orlandi, Marcelo Ornaghi [UNESP] (Elsevier, 2024)
Developing sunlight-driven catalysts is an attractive strategy for conversion of solar energy into chemical fuel. This work describes the synthesis of g-C3N4/Sn3O4 photoanodes by a microwave-assisted hydrothermal method, for hydrogen (H2) generation. The structural analysis of the materials was investigated using XRD, Raman and FTIR spectroscopies. The chemical composition and valence state were analyzed using XPS, while the morphologies were characterized through FESEM and TEM. The magnitude of absorption for the g-C3N4/Sn3O4 sample increased as observed using UV–Vis. An excellent H2 production of 0.49 mmol/L within 3 h, at 0.8 V vs. Ag/AgCl, was achieved using the g-C3N4/Sn3O4 heterostructure as a photoanode, which was nearly 4.4 and 4.8 times higher, respectively, compared to the H2 production obtained using g-C3N4 and Sn3O4 individually. The photoelectrochemical (PEC) results demonstrated that the g-C3N4/Sn3O4 photoanode presented higher charge carrier mobility and photocurrent density, compared to the individual materials. The optimal heterostructure exhibited a solar-to-hydrogen (STH) energy conversion efficiency of 0.49 %, as well as high stability. The success of the heterostructure could be ascribed to the interfacial contact between the g-C3N4 and Sn3O4 semiconductors, with photogenerated electrons flowing from the g-C3N4 to the Sn3O4 surface, minimizing electron/hole pair recombination. This work provides a reference for the design of heterostructures composed of Sn3O4 joined to carbon-based materials that can provide high performance in H2 generation.
Keywords: Graphitic carbon nitride; Hydrogen evolution reaction; Photoelectrochemical properties; Tin oxide